2016
DOI: 10.18203/2349-2902.isj20163596
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of intra-operative bile cultures with septic complications following biliary tract surgery

Abstract: INTRODUCTIONRoutine intra-operative bile culture during biliary tract surgeries is a common practice among hepatobiliary surgeons. This is based on reports that bactibilia is a predictor of septic complications following these surgeries. 1,2Most of these studies have focused on impact of pre-operative biliary drainage on the biliary microflora and its resulting infectious complications. Bile-contaminated operations are reported to have a higher incidence of septic complications than non-bilecontaminated operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In contrast to our study, a recent study conducted in India concluded with the insignificant association of a positive bile culture with the risk of surgical site infections after biliary tract surgery. 16 Though we did not take bile culture and compare it with the pus culture from SSI, we did focus on the prophylactic approach to prevent SSI after the incidence of bile spillage. Our study has also documented a higher incidence of SSI after bile spillage than clean surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, a recent study conducted in India concluded with the insignificant association of a positive bile culture with the risk of surgical site infections after biliary tract surgery. 16 Though we did not take bile culture and compare it with the pus culture from SSI, we did focus on the prophylactic approach to prevent SSI after the incidence of bile spillage. Our study has also documented a higher incidence of SSI after bile spillage than clean surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another study concluded that in patients with positive bile culture who develop surgical site infections, two-thirds of them are caused by different strains. 16 This means that port-site infections after laparoscopic cholecystectomy can be caused by contamination of both bile and surroundings and a wide range of microbes are responsible for them. Therefore, just using a prophylactic antibiotic against microorganisms present in bile cannot solve our problem.…”
Section: Discussionmentioning
confidence: 99%